COMPARISON OF INDONESIAN HEALTH LAW WITH INTERNATIONAL HEALTH REGULATIONS: A LITERATURE STUDY - Shohib Muslim (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyse the comparison between the Indonesian Health Law and international health regulations, especially those issued by the World Health Organization (WHO). The literature review shows that the Indonesian Health Law is oriented towards the fulfilment of public health rights aligned with national development priorities, while international regulations prioritise global standards and universal, evidence-based approaches. This difference creates challenges in implementation, especially related to limited resources and infrastructure at the national level. Nevertheless, opportunities for integration through adaptation of local policies with international guidelines can provide significant benefits in improving the quality of health services and response to global health threats. This research highlights the importance of collaboration between national policies and global standards to strengthen the health system in Indonesia.